A Debreceni Egyetem Centenáriumi Év programsorozatának nyitó rendezvénye - Béres, Zsuzsa (Gerundium, 2012)
THE OPENING EVENT OF THE SERIES OF PROGRAMS COMMEMORATING THE CENTENNIAL OF THE UNIVERSITY OF DEBRECEN, FEBRUARY 3–4, 2012. A commemorative session of the University Senate, the inauguration of a memorial plaque, the opening of an exhibition, a theatrical world premier, and an evening ball were part of the opening program of the centenary year with which the University of Debrecen celebrated the onehundredth anniversary of the foundation of its legal predecessor, the Royal Hungarian University of Debreczen. he brief summary below will evoke the respective events of the series of pertinent events.